Organization and Management of the Innovative Activity of Teachers in the Educational System - Donaboyeva Ziyoda Mukhiddin kizi (Researchparks Publishing, 2023)
In this article, the following considerations are explained: the organization, and management of the innovative activities of pedagogues in the educational system, the changes taking place in the economic, social, political, and cultural spheres of our society depend on the educational system, which determines the intellectual potential of our country in the future and is considered the main condition for its development.